Large‐Eddy Simulation of a katabatic jet along a convexly curved slope: 2. Evidence of Görtler vortices. Issue 10 (24th May 2017) - Brun, Christophe
Abstract: This paper is the second part of a study of katabatic jet along a convexly curved slope with a maximum angle of about 35.5°. Large‐Eddy Simulation (LES) is performed with a special focus on the outer‐layer shear of the katabatic jet. In the first part, a basic statistical quantitative analysis of the flow was performed. Here a qualitative and quantitative description of vortical structures is used to gain insight in the present 3‐D turbulent flow. It is shown that Görtler vortices oriented in the streamwise downslope direction develop in the shear layer. They spread with a specific mushroom shape in the vertical direction up to about 100 m height. They play a main role with respect to local turbulent mixing in the ground surface boundary layer. The present curved slope configuration constitutes a realistic model for alpine orography. This paper provides a procedure based on local turbulence anisotropy to track Görtler vortices for in situ measurements, which has never been proposed in the literature. Key Points: Occurrence of Görtler streamwise vortices in an LES of katabatic jet along a curved slope involving large‐scale vortical structures Use of local turbulence anisotropy as a tool for Görtler vortices identification and turbulent mixing detection for in situ measurements